(untitled) (Ustozlar uchun, 2025)
This article provides a comprehensive overview of the structure of English as a Foreign Language (EFL) classes. It discusses the fundamental components of lesson design, the stages of language teaching, and the integration of language skills. The study examines traditional and modern teaching methodologies, including Communicative Language Teaching (CLT) and Task-Based Learning (TBL), as well as the role of digital technologies in EFL instruction. The paper concludes that a well-structured lesson—characterized by clear objectives, learner-centered interaction, and skill integration—is essential for successful English language learning.